Exploring The Foreign Market Entry Strategy from Ornamental Plant SME in Batu City - Fakhriyyah, Dewi Diah; , Sudarmiatin (Rescollacom (Research Collaborations Community), 2024)
This research examines the importance of exploring foreign market entry strategies for Small and Medium Enterprises (SMEs) by a case study of Creative Kokedama, an SME that developed product innovations from ordinary flowering plants into ornamental plant kokedama and successfully penetrated the Japanese market, the country origin of kokedama. The research findings indicate that the main motivation for Creative Kokedama to expand into the international market is intrinsic motivation. The owner reasoned that kokedama plant crafts originated from Japan, so she wanted to bring kokedama back to Japan. She has his own satisfaction when she is able to bring kokedama to the Japanese market. That motivation can related to psychological factors, such as the desire for self-development and global recognition, as well as ethnocentrism, which is pride in local cultural values reflected in the kokedama products. The entry mode chosen is direct exporting, which does not go through an intermediary, but directly to foreign buyer. Japan was chosen as the export destination country because Japan is the origin country of kokedama. Although previously it had also exported to Malaysia, Brunei Darussalam, and Singapore. Selection of export destination country can be related to pull factor theory in internationalization, Japan as the country of origin for kokedama, may have a high appreciation for products with unique approaches or modifications. This research contributes to the literature on SME internationalization strategies by offering insights into the importance of the combination of product innovation and intrinsic motivation especially psychological factors in achieving export success. Moreover, these findings can also serve as practical guidance for other SMEs looking to enter the global market through innovation and locally value-based strategies.